(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Waste Land is a poem by T. S. Eliot, widely regarded as one of the most important poems of the 20th century and the work between modern poetry. Published in 1922, this 434-line poem first appeared in the United Kingdom in the October issue of Eliot’s The Criterion and in the United States in the November issue of The Dial. It was published by a book in December 1922. Among its most famous sentences are April is a very cruel month, I will show you fear in a little dust, and mantra in the Sanskrit language Shantih shantih shantih.